Exercise in Perspective-Taking: First Nations Version of the New Testament - Muehlhoff, Tim (Christian scholar's review, 2025)
The First Nations Version presents the Scriptures through the perspective of Native North American storytellers who view Jesus and biblical truth through their own rich cultural lens and language. “Our priority,” state the editors, “has been to maintain the accuracy of the translation and its faithfulness to the intended meaning of the biblical writers within a First Nations context.” The following asks us to consider what it means to dress for spiritual battle not from a Roman solider context, but a First Nation warrior; or to see the New Jerusalem not as a Middle Eastern city, but a Sacred Village coming down from the Great Spirit. Such perspective-taking makes the Christian mosaic of ethnicities come alive in fresh ways.